2012
DOI: 10.1016/j.clinph.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Limb segment vibration modulates spinal reflex excitability and muscle mRNA expression after spinal cord injury

Abstract: Objective We investigated the effect of various doses of vertical oscillation (vibration) on soleus H-reflex amplitude and post-activation depression in individuals with and without SCI. We also explored the acute effect of short-term limb vibration on skeletal muscle mRNA expression of genes associated with spinal plasticity. Methods Six healthy adults and five chronic complete SCI subjects received vibratory stimulation of their tibia over three different gravitational accelerations (0.3g, 0.6g, and 1.2g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…We previously confirmed that the vibration intervention mimicked the mechanical input conditions of previous animal studies [19] and that it did not cause reflexive muscle contractions [30, 31]. We used a novel and sophisticated imaging approach to obtain outstanding imaging resolution for in vivo bone adaptations.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We previously confirmed that the vibration intervention mimicked the mechanical input conditions of previous animal studies [19] and that it did not cause reflexive muscle contractions [30, 31]. We used a novel and sophisticated imaging approach to obtain outstanding imaging resolution for in vivo bone adaptations.…”
Section: Discussionsupporting
confidence: 60%
“…These parameters were selected to reflect the vibration conditions of recent studies that reported anabolic effects of vibration in the murine tibia [11, 13, 29]. We previously verified that vibration using these parameters does not increase background EMG activity [30] and downregulates monosynaptic reflex activity [31]. Reflex-mediated muscle contractions did not occur, eliminating muscle force as a potential confounding source of mechanical load to the bone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration is also being investigated as a method to reduce spasticity [2, 14], one of the most prevalent and bothersome secondary heath conditions of SCI [6]. Our previous work has characterized the acute neurophysiologic response to vibratory load after SCI [5]. We observed a long-lasting (>1 minute) enhancement of H-reflex post-activation depression after acute vibration of a constrained limb segment.…”
Section: Introductionmentioning
confidence: 84%
“…To quantify post-activation depression of H2, we calculated the depression ratio: 100* (HB – H2) / HB. Our previous work [5] indicated that during vibration in participants with SCI, H1 is unstable and is occasionally absent. This limits its suitability in calculations of H2 depression.…”
Section: Methodsmentioning
confidence: 99%